AN ANALYSIS OF MUSIC PERFORMANCE AND ENTERTAINMENT IN ULU SIAU SOCIETY - Ade Patras Mamontho; Luccylle Takalumang; Sri Sunarmi (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This study aims to investigate the variation of music presentation in Kafe Pelangi, Ulu Siau, Sitaro Regency, and its impact. The research method applied is a qualitative method with data collection techniques through observation, interviews, and document analysis. The collected data were classified, interpreted, and described using words. The results show that the presentation of music at Kafe Pelangi involves live performances and bands, which are supported by musical instruments, makeup, clothing, stage, and sound system. The variety of music presented includes slow pop, pop rock, jazz, dangdut, keroncong, R&B (Rhythm and Blues), and cha-cha. The function of the music presentation involves attracting visitors, providing livelihoods for musicians, and providing entertainment for visitors at Kafe Pelangi Ulu Siau.